Adobe Photoshop CC Classroom in a Book (2018 release) : classroom in a book - Faulkner, Andrew; Chavez, Conrad (Classroom in a book., 2018)
Creative professionals seeking the fastest, easiest, most comprehensive way to learn Adobe Photoshop choose Adobe Photoshop CC Classroom in a Book (2018 release) from Adobe Press. The 15 project-based lessons show key step-by-step techniques for working in Photoshop, including how to correct, enhance, and distort digital images, create image composites, and prepare images for print and the web. In addition to learning the essential elements of the Photoshop interface, this revised edition for the 2018 release covers features like search capabilities, Content-Aware Crop, Select and Mask, Face-Aware Liquify, designing with multiple artboards, creating and organizing enhanced brush presets, and much more! The online companion files include all the necessary assets for readers to complete the projects featured in each chapter as well as ebook updates when Adobe releases relevant new features for Creative Cloud customers. All buyers of the book get full access to the Web Edition: a Web-based version of the complete ebook enhanced with video and multiple-choice quizzes.